The Fragility of Things : Self-Organizing Processes, Neoliberal Fantasies, and Democratic Activism - Connolly, William E. (Book collections on Project MUSE., 2013)
Seeking to extend sensitivity to the world's fragilities and intensify democratic activism, William E. Connolly explores how neoliberal capitalism collides with the fragile self-organizing systems that help to constitute our world.